Membrane bioreactors for wastewater treatment. - Stephenson, Tom, ....-; Jefferson, Bruce, ....-; Judd, Simon, ....- (London : IWA, 2006)
Membrane Bioreactors for Wastewater Treatment covers the subject of membrane bioreactors (MBR) for wastewater treatment, dealing with municipal as well as industrial wastewaters. The book details the 3 types of MBR available and discusses the science behind the technology, their design features, operation, applications, advantages, limitations, performance, current research activities and cost. As the demand for wastewater treatment, recycling and re-use technologies increases, it is envisaged that the membrane separation bioreactor will corner the market. Contents Membrane Fundamentals Biological Fundamentals Biomass Separation Membrane Bioreactors Membrane Aeration and Extractive Bioreactors Commercial Membrane Bioreactor Systems Membrane Bioreactor Applications Case Studies
Keywords: Afvalwaterzuivering; Bioreactoren; Membraantechnologie